IDENTIFICATION OF ASPECTS RELATED TO A CONTINUOUS IMPROVEMENT PROJECT - Cicero da Silva, Luciano; Eduarda Leão Berzoti de Andrade, Maria; Cristina Ferreira Clemente Silva, Milena; Grazielly Sousa Santos, Rayonária (Revista Gênero e Interdisciplinaridade, 2023)
This review presents the monograph ‘’Identification of aspects related to a continuous improvement project’’, written by Mariana Roque Tognetti, published by the Course Conclusion Work or Dissertation or Thesis presented to the Faculdade de Gestão e Negócios da Universidade Federal de Uber-lândia as partial requirement for obtaining the title of Bachelor in Administration. The monograph presented by the author seeks to present a comprehensive review of the existing literature on the subject, as well as a detailed case study of a specific company. From the notes revealed in the monograph, we realize that it is important for an organization to implement tools and methods that help them identify and solve both internal and external problems. As mentioned by the author, gaps were identified in the company that was used for the field research. The author believes that the method used caused impacts on the organization, and observed that the external aspects were also present, taking into consideration how much the team was impacted by the implemented project.